Konsep Pendidikan KH. Imam Zarkasyi dan Relevansinya dengan Pembelajaran Bahasa Arab - AT, Muzdalifa; Mukhtar, Mukhtar; Zulkiflih, Zulkiflih; R, Rahmat; Munawarah, Munawarah (Al-Abshar: Journal of Islamic Education Management, 2024)
This study aims to examine the concept of education of KH. Imam Zarkasyi and its relevance to Arabic language learning at the Sheikh Hasan Yamani Islamic Boarding School Campalagian District Polewali Mandar Regency. The concept of KH. Imam Zarkasyi rests on educational goals that want to make students not only understand the lesson, but more than that, practice and preach it. To achieve this goal, he made the concept of integral education between religious and general subjects. This is what the Sheikh Hasan Yamani Islamic Boarding School tried to adopt in learning Arabic so that it is interesting to study the extent of its relationship.Furthermore, the research method used in this research is qualitative research whose type is included in field research. Data collection in the study through interviews with research informants. Then analyzed using three stages, namely: 1) Data reduction, 2) Presentation of data, and 3) Data verification and conclusion drawing. The results showed that the concept of education of KH. Imam Zarkasyi showed an update in the field of education, starting from the renewal of the pesantren curriculum, system and language teaching methods, especially in Arabic language learning, namely by applying the direct method or direct method which leads to active language mastery by increasing practice, both oral and written. The relevance between Arabic language learning at Pondok Hasan Yamani and the concept of KH. Imam Zarkasyi's education lies in the goals, systems, methods, and curriculum that have in common in an effort to produce students who are fluent in Arabic and able to understand and spread the teachings of Islam well.